Digital Learning Dynamics: The KesPro-P App and Its Effect on The Behavioral Intention of Nursing Students - Herien, Yelly; Fajria, Lili; Wahyu, Wedya; Sari, Ira Mulya (JENDELA NURSING JOURNAL, 2024)
Background: understanding behavioral intention is crucial for effective learning media design and promoting technology use in education and nursing. The KesPro-P app, developed for reproductive health nursing practicals, is introduced, with a focus on evaluating nursing students' behavioral intention, influenced by perceived usefulness and ease of usePurpose: the purpose of the study was to find out how 50 fifth semester nursing students who participated in the Reproductive Health Nursing practicum's behavioral intention was affected by utilizing the KesPro-P application.Methods: this cross-sectional study was carried out from September to October 2023 at Faculty of Nursing, Universitas Andalas Indonesia. Students that participated in the research completed questionnaires for research variables and used the KesPro-P program. The Spearman Rank Test was used to process the data using SPSS.Results: perceived usefulness, perceived ease of use, and behavioral intention were found to be valuable among students who had a high propensity to use the KesPro-P application. Perceived usefulness, perceived ease of use, and behavioral intention are significantly correlated (p = 0.000).Conclusion: students believe this App is helpful when used in lectures and is effective, efficient, and simple to use anywhere, at any time, as evidenced by the high perceived usefulness and perceived ease of use ratings. In order to have all of the student practicum competences for this course incorporated in a single application, this application has to be developed further for more practicum topics.